Inventory Management Strategy Using the ABC Analysis Method - Ratna Suminar (Journal of Industrial and Engineering System, 2026)
Inventory control is crucial for the operational process in after-sale company. Determining the quality of materials is used to ensure production runs is suitable to the planned schedule. This study aims to determine inventory according to a more strategic due to material classification. The classification based on the highest annual usage rate to reduce storage costs and material limitation. This company's problem is the storage cost expenditure due to the existence of materials that can no longer be used (deadstock) amounting to IDR 13,233,620, and this cost will continue to increase if the materials cannot be used. Therefore, this study used the ABC analysis method, supported by determining the amount of safety stock and Re-Order Point. This method utilizes the Pareto principle (80/20). The results are 73% of all material costs are concentrated in category A (IDR70,403,380), classification in category B is IDR18,485,856 equivalent to 19% and the total cost in category C is IDR8,544,500 equivalent 8.8%. This study contributes to the company's development of inventory control strategy includes the provision of safety stock and appropriate quantity to determine the timing of reorders for needed item, taking into account lead times when placing orders.